Incidence of contralateral cervical metastasis in laryngeal tumors - Arthur Paredes Gatti; Juliana Cristina Pacheco; Nicolas Galat Ahumada; Carlos Neutzling Lehn; Fernando Walder (Brazilian Journal of Otorhinolaryngology)
Objective: To evaluate if patients with laryngeal SCC homolateral cN+ and contralateral cN− should be submitted to bilateral neck dissection. Methods: The team reviewed medical records from 135 patients with a diagnosis of laryngeal malignancy between March/2009 and September/2017, analyzing gender, age, tobacco and alcohol comsumption, primary tumor site, neck dissection laterality, clinical and pathological contralaterality, staging, tumor recurrence or late metastasis and survival Results: We observed that 40.74% were pN+ on at least one side after neck dissection, which 87.27% performed bilateral neck dissection. Of these, 66.67% did not have contralateral metastasis, 87.5% had no previously clinically evident metastasis. Conclusion: Patients contralateral cN− have a risk <20% for occult metastasis and should not routinely go through bilateral neck dissection. Level of evidence: Level III.